2014
DOI: 10.1016/j.molcel.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of Active Bax at the Membrane

Abstract: Bax plays a central role in the mitochondrial pathway of apoptosis. Upon activation, cytosolic Bax monomers oligomerize on the surface of mitochondria and change conformation concertedly to punch holes into the outer membrane. The subsequent release of cytochrome c initiates cell death. However, the structure of membrane-inserted Bax and its mechanism of action remain largely unknown. Here, we propose a 3D model of active Bax at the membrane based on double electron-electron resonance (DEER) spectroscopy in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

35
313
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(348 citation statements)
references
References 42 publications
35
313
0
Order By: Relevance
“…Our data show that during apoptosis, the N-segment and a1 of Bak dissociate entirely from the rest of the protein to expose the BH4 domain and other residues (Fig. 9b), consistent with recent reports that Bak a1 and a6 became 450 Å apart after tBid treatment in LUV 26 and the distance between Bax a1 and a2 varies widely after activation 21 . Disulfide tethering of Bak showed that a1 dissociation from both the core (a2-a5) and the latch (a6-a8) was required for pore formation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data show that during apoptosis, the N-segment and a1 of Bak dissociate entirely from the rest of the protein to expose the BH4 domain and other residues (Fig. 9b), consistent with recent reports that Bak a1 and a6 became 450 Å apart after tBid treatment in LUV 26 and the distance between Bax a1 and a2 varies widely after activation 21 . Disulfide tethering of Bak showed that a1 dissociation from both the core (a2-a5) and the latch (a6-a8) was required for pore formation.…”
Section: Discussionsupporting
confidence: 92%
“…Another key conformation change identified in Bak and Bax is separation of the latch (a6-a8) from the core (a2-a5) 19,20 . After these large changes in conformation, the proteins form BH3:groove dimers and make significant contact with the outer membrane surface 9,16,19,21,22 .…”
mentioning
confidence: 99%
“…29,67 Furthermore, the α6-α9 region in oligomerized Bax was found to be extended 29 and flexible. 67 Notably, Bleicken et al 67 suggested the α9:α9 interaction 'within' dimers may be anti-parallel based on a model in which the α2-α5 core dimers position on the rim of the pore rather than facing the cytosol.…”
Section: Discussionmentioning
confidence: 94%
“…29,67 Furthermore, the α6-α9 region in oligomerized Bax was found to be extended 29 and flexible. 67 Notably, Bleicken et al 67 suggested the α9:α9 interaction 'within' dimers may be anti-parallel based on a model in which the α2-α5 core dimers position on the rim of the pore rather than facing the cytosol. Although our linkage studies and the FRET studies of Gahl et al 29 show parallel interaction of the α9 helices, we may be detecting interactions 'between' dimers (as depicted in Figure 7d) and not the interactions that might occur 'within' dimers.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation